Pensiones : del descontento a las soluciones - Valdés Prieto, Salvador (Ediciones Universidad Católica de Chile, 2018)
1,084 / 5,000Translation results. Although the pension situation starts from a delicate situation, there are many areas where progress is possible. The representative amount of pensions is close to 164 thousand [dollars] per month. How much would be a reasonable pension, taking into account that other people in the household also contribute? Faced with this question, the most representative response among those 65 years of age or older was 375,000 [dollars] per month. However, the representative labor income of the current workers, who are his children, is 400,000 [dollars] per month. This pension aspiration is 94% of the children's income. That aspiration is also close to 200% of your own income during your past working life. This gap is the fuel that the No + AFP movement uses. This is one of the bases of the diagnosis of the Better Pensions for Chile study group, convened by the economist Salvador Valdés at Clapes UC. It is about thirteen psychologists, social communicators, economists, lawyers and experts in public opinion, who analyze how to reduce this gap in a few years, not in 30 more years.